CommunityDacquired pneumonia in chronic heart failure patients: prevalence and risk factors - N. E. Romanova; B. A. Sidorenko; V. E. Nonikov; I. A. Sharoshin; D. V. Preobrazhensky (Российский кардиологический журнал)
.